Social learning and monetary policy at the effective lower bound - Jasmina Arifovic; Alex Grimaud; Isabelle Salle; Gauthier Vermandel (Bank of Canada, 2020)
The first contribution of this paper is to develop a model that jointly accounts for the missing disinflation in the wake of the Great Recession and the subsequently observed inflation-less recovery. The key mechanism works through heterogeneous expectations that may durably lose their anchorage to the central bank (CB)'s target and coordinate on particularly persistent below-target paths. We jointly estimate the structural and the learning parameters of the model by matching moments from both macroeconomic and Survey of Professional Forecasters data. The welfare cost associated with those dynamics may be reduced if the CB communicates to the agents its target or its own inflation forecasts, as communication helps anchor expectations at the target. However, the CB may lose its credibility whenever its announcements become decoupled from actual inflation, for instance in the face of large and unexpected shocks.
Keywords: C82; E32; E52; E70; 330; Monetary policy; Monetary policy communication; Credibility; Central bankresearch; Economic models; Business fluctuations and cycles